(untitled) (Journal of Science and Technology Research, 2026)
The production of biodiesel from waste cooking oil (WCO) represents a sustainable and environmentally friendly approach to waste management and renewable energy generation. This study explores the use of calcium oxide (CaO) nanocatalyst in the transesterification process of converting WCO into biodiesel. CaO nanocatalyst is favored for its high catalytic activity, low cost, and environmental compatibility. In this study, calcium oxide (CaO)-based nano-catalyst was prepared through calcination process using local waste eggshells to produce biodiesel. The nano-CaO catalysis impact was investigated in a two-step transesterification chemical reaction from waste cooking oil (WCO) to biodiesel. Transmission electron microscope (TEM), Fourier transform infrared (FT-IR) spectroscopy and X-ray diffraction (XRD) techniques were utilized to confirm the CaO nano-catalyst. It was discovered that the CaO catalyst made from eggshell waste was an efficient, stable, and reasonably priced heterogeneous catalyst to be highly effective for the manufacture of biodiesel. The production of biodiesel was confirmed through FTIR analysis. Moreover, the biodiesel properties such as calorific value, specific gravity, acid value, density, flash point, kinematic viscosity, ash content, water content and cetane number were investigated and found to be similar with the EN 14214 biodiesel standard. It is expected that producing biodiesel using eggshell as a heterogeneous catalyst offers an economical and sustainable method of producing green fuel. This study underscores the potential of CaO nanocatalyst in enhancing the efficiency and sustainability of biodiesel production, offering a viable solution for waste management and energy production. J. of Sci. and Tech. Res. 6(2): 33-41, 2025